PML‐RARA fusion resulting from a cryptic insertion of RARA gene into PML gene without the reciprocal RARA‐PML fusion: clinical, cytogenetic, and molecular characterization and prognosis. (26th April 2014) - Fan, Hongxin; Ortega, Veronica; Fanasch, Hilal M.; Wang, Yao; Holder, Kenneth N.; Higgins, Russell A.; Mendiola, Christina; Mohamed, Gihan; Vadlamudi, Kumari; Velagaleti, Gopalrao
Abstract We describe a case of acute promyelocytic leukemia in a 61‐yr‐old woman with a cryptic insertion of RARA gene into PML gene. Using a combination of cytogenetic and molecular methods, we confirmed the insertion and presence of the PML‐RARA transcript and lack of the reciprocal RARA‐PML transcript. Although such cryptic insertions leading to a PML‐RARA fusion have been previously reported, we show that such variant insertions, based on our case, appear to have the same prognostic significance as the classical t(15;17)(q22;q21).